Modified bentonite drilling fluid for drilling and preparation method thereof
Patent Information
- Application Number
- CN202010920458.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-04
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2040-09-04
AI Technical Summary
[0005]上述钻井液在制备后使用时一方面改性加入的试剂过多,甚至有的有毒,或危险性高;有的改性过程过于复杂
[0028] The beneficial effects of this invention are as follows: In preparing drilling fluid, the raw materials containing bentonite and photomodified powder are first subjected to multiple freeze-thaw cycles and stirring. Water loss at low temperatures further reduces the molecular bonding strength within the raw materials, resulting in more thorough mixing of the photomodified powder and bentonite, achieving nanoscale contact. This also improves the adjustment effect during thickening and other adjustments. Subsequently, further modification using sunlight exposure or ultraviolet irradiation adjusts the surface charge properties of the raw materials, leading to faster fluid formation, better fluid yield, stronger sand-coating ability, lower filtration loss, and better stability after the addition of thickeners such as surfactants, flow modifiers, and pH adjusters.
Smart Images

Figure CN111995993B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of bentonite, and in particular to a modified bentonite drilling fluid for drilling and its preparation method. Background Technology
[0002] Bentonite is a non-metallic mineral with montmorillonite as its main mineral component. Montmorillonite has a 2:1 crystal structure consisting of two silicon-oxygen tetrahedra sandwiching a layer of aluminum-oxygen octahedra. Due to the presence of certain cations such as Cu, Mg, Na, and K in the layered structure of the montmorillonite unit cells, and the fact that these cations are unstable with the montmorillonite unit cells and easily exchanged with other cations, it exhibits good ion exchange properties. Its specific layered structure gives it a large specific surface area, resulting in strong adsorption. Furthermore, the presence of hydrophilic OH groups gives it excellent dispersibility, suspension, and binding properties in aqueous solutions. Within a certain concentration range, it exhibits excellent thixotropy. That is, when externally stirred, the suspension behaves as a highly fluid sol; after stirring stops, it spontaneously arranges itself into a three-dimensional network gel structure without sedimentation or water separation. This characteristic is particularly suitable for preparing drilling mud. Commonly used methods for modifying bentonite include sodium modification, acid modification, calcination modification, salt modification, organic modification, inorganic pillar modification, and inorganic / organic composite modification.
[0003] Patent CN103482638A discloses a method for manufacturing organic bentonite, including the following steps: 1) pulping; 2) settling; 3) removing sand using a hydrocyclone separator; 4) further filtering solid impurities using a horizontal centrifuge; 5) liquid-liquid separation using a disc centrifuge to obtain concentrated sodium-based montmorillonite slurry; 6) determining solid content; 7) adding soda ash; 8) heating, adding sulfuric acid to adjust pH, and maintaining the temperature; 9) organic coating reaction: adding white oil and octadecyltrimethylammonium chloride; 10) pressing dry; 11) drying.
[0004] Patent CN107777696A discloses a method for preparing organic bentonite. Calcium-based bentonite is ground to a fineness of 100-325 mesh using a Raymond mill, water is added to form a slurry, sodium carbonate is added and mixed evenly, and the mixture is aged to obtain a sodium-based bentonite slurry. The sodium-based bentonite slurry and polyacrylamide are added to a reaction vessel for reaction, filtered under pressure, and then transferred to a modifying machine. Dibutyl phthalate and an emulsifier are added to the modifying machine for modification, followed by drying. The mixture is then added to a mixing machine and mixed with dimethyloctadecylbenzylammonium chloride to obtain organic bentonite.
[0005] The drilling fluids mentioned above, when used after preparation, often involve excessive amounts of added reagents during modification, some of which are toxic or highly dangerous; some modification processes are also overly complex. Moreover, in actual use, due to the poor compatibility of bentonite with other reagents, sedimentation and water segregation inevitably occur after prolonged standing time.
[0006] Laser irradiation and ablation are high-efficiency modification methods proposed in recent years. They are safe, non-toxic, and highly controllable, and the high laser energy allows for processing materials down to the nanometer level, making them widely used in the preparation of various colloids. Furthermore, zinc oxide and titanium oxide are highly efficient photomodification materials, especially nanoscale zinc oxide and titanium oxide, which have high specific surface areas. After absorbing light, they can directly induce electron transfer, thereby modulating their charge properties. Summary of the Invention
[0007] In view of the above, and to solve the problems of the prior art, this application provides a modified bentonite drilling fluid for drilling, comprising the following components: bentonite, viscosifier, filtration reducer, flow modifier, plugging agent, weighting agent, light-modifying powder, pH adjuster, lubricant, and water;
[0008] The tackifier is one or more of xanthan gum, amine oxide, and polyvinylpyrrolidone; the filtration loss reducer is one or more of sulfomethylphenol resin and lignite resin; the flow pattern regulator is polyamide LH-OWA or polyamide LH-ORM; the weighting agent is barite; the photomodifying powder is nano-ZnO or nano-TiO2; the pH adjuster is a mixture of sulfuric acid, polyvinyl alcohol, sodium silicate, and sodium carbonate; and the lubricant is graphite powder or silica nanospheres.
[0009] The composition, by weight, consists of 5-8 parts bentonite, 2-3 parts thickener, 2-3 parts filtration loss reducer, 3-5 parts flow modifier, 2-5 parts sealing agent, 40-50 parts weighting agent, 10-15 parts light-modifying powder, 5-8 parts pH adjuster, 1-2 parts lubricant, and 100 parts water.
[0010] On the other hand, a method for preparing the modified bentonite drilling fluid for drilling includes the following steps:
[0011] Step 1: Mix and stir the raw materials
[0012] First, mix bentonite, filtration loss reducer, sealing agent, lubricant, weighting agent and light-modifying powder. After mixing, use a high-speed mixer to stir and mix for more than 1 hour. Then add an equal weight of water and mix. Stir for more than 1 hour after mixing.
[0013] Step 2, Freeze-forming
[0014] The mixture obtained in step 1 is frozen at -20°C for 10 hours. The frozen product is then thawed at room temperature with ventilation, and after thawing, it is stirred and pulverized.
[0015] Step 3: Photoirradiation modification
[0016] The product from step 2 is subjected to multiple freeze-thaw cycles until its moisture content is below 30%. Then, it is spread out to a thickness of less than 5 cm and placed in the sun with a moisture content of 30-35% for more than 100 hours, turning it over every 10 hours. The average power density of the sunlight should be greater than 30 W / m2. Alternatively, ultraviolet laser irradiation for more than 50 hours can be used instead of sun exposure, turning it over every 5 hours. During laser irradiation, the laser power density should be greater than 50 W / m2 and the laser wavelength should be less than 300 nm. Water should be added to supplement the moisture content if it is insufficient during the modification process.
[0017] Step 4: Add the modified product from Step 3 to the thickener, flow modifier, pH adjuster, and water, and mix thoroughly to obtain the modified bentonite drilling fluid.
[0018] The photomodified powder is nano-ZnO or nano-TiO2 with a particle size of less than 200nm.
[0019] The preparation method of the photomodified powder is as follows:
[0020] Step A: Mix industrial zinc oxide or titanium dioxide powder with 10 times its volume of water, wherein the purity of the zinc oxide and titanium dioxide raw materials is higher than 98%;
[0021] Step B: Place the product after mixing in step A in a stirrer and stir it at high speed. Then place it under an infrared pulsed laser for ablation preparation. The laser single pulse energy is required to be greater than 100 J / cm2, the laser repetition frequency is greater than 500 Hz, the ablation time is greater than 10 hours, and the particle size is processed until it is less than 200 nm.
[0022] Step C: Dry the product from step B.
[0023] Alternatively, the preparation method of the photomodified powder is as follows:
[0024] Step A: Mix industrial zinc powder or titanium powder with 15 times its volume of water, wherein the purity of the zinc powder or titanium powder raw materials is higher than 95%;
[0025] Step B: Place the product from Step A into a stirrer and stir it at high speed. Then place it under an infrared pulsed laser for ablation. The laser single pulse energy should be greater than 100 J / cm2, the laser repetition frequency should be greater than 500 Hz, and the ablation time should be greater than 10 hours. Process until the particle size is less than 200 nm. Keep the water temperature below 30℃ during ablation.
[0026] Step C: Dry the product from step B.
[0027] The infrared laser is a carbon dioxide laser.
[0028] The beneficial effects of this invention are as follows: In preparing drilling fluid, the raw materials containing bentonite and photomodified powder are first subjected to multiple freeze-thaw cycles and stirring. Water loss at low temperatures further reduces the molecular bonding strength within the raw materials, resulting in more thorough mixing of the photomodified powder and bentonite, achieving nanoscale contact. This also improves the adjustment effect during thickening and other adjustments. Subsequently, further modification using sunlight exposure or ultraviolet irradiation adjusts the surface charge properties of the raw materials, leading to faster fluid formation, better fluid yield, stronger sand-coating ability, lower filtration loss, and better stability after the addition of thickeners such as surfactants, flow modifiers, and pH adjusters.
[0029] The photomodified powder used is prepared by laser ablation. No other raw materials are introduced during the preparation process. It can directly ablate metals or their oxides to obtain the product. It has a high yield, is safe and pollution-free, does not affect the modification of bentonite, and is also suitable for other industrial applications. Attached Figure Description
[0030] The accompanying drawings, included to provide a further understanding of the disclosed subject matter, are incorporated into and form part of this specification. The drawings also illustrate the implementation of the disclosed subject matter, and, together with the detailed description, serve to explain the principles of its implementation. No attempt is made to demonstrate excessive structural detail to provide a basic understanding of the disclosed subject matter and its various practical applications.
[0031] Figure 1 This is a flowchart illustrating the modification process of the present invention;
[0032] Figure 2 This is a flowchart of the photomodified powder processing of the present invention.
[0033] Figure 3 This is another processing flow diagram of the photomodified powder of the present invention. Detailed Implementation
[0034] The advantages, features, and methods of achieving the stated objectives of this invention will become clear from the accompanying drawings and the following detailed description.
[0035] Example 1:
[0036] Combination Figure 1 This application provides a modified bentonite drilling fluid for drilling, comprising the following components: bentonite, viscosifier, filtration reducer, flow modifier, plugging agent, weighting agent, light-modifying powder, pH adjuster, lubricant, and water;
[0037] The tackifier is one or more of xanthan gum, amine oxide, and polyvinylpyrrolidone; the filtration loss reducer is one or more of sulfomethylphenol resin and lignite resin; the flow pattern regulator is polyamide LH-OWA or polyamide LH-ORM; the weighting agent is barite; the photomodifying powder is nano-ZnO or nano-TiO2; the pH adjuster is a mixture of sulfuric acid, polyvinyl alcohol, sodium silicate, and sodium carbonate; and the lubricant is graphite powder or silica nanospheres.
[0038] The composition, by weight, consists of 5-8 parts bentonite, 2-3 parts thickener, 2-3 parts filtration loss reducer, 3-5 parts flow modifier, 2-5 parts sealing agent, 40-50 parts weighting agent, 10-15 parts light-modifying powder, 5-8 parts pH adjuster, 1-2 parts lubricant, and 100 parts water.
[0039] On the other hand, a method for preparing the modified bentonite drilling fluid for drilling includes the following steps:
[0040] Step 1: Mix and stir the raw materials
[0041] First, mix bentonite, filtration loss reducer, sealing agent, lubricant, weighting agent and light-modifying powder. After mixing, use a high-speed mixer to stir and mix for more than 1 hour. Then add an equal weight of water and mix. Stir for more than 1 hour after mixing.
[0042] Step 2, Freeze-forming
[0043] The mixture obtained in step 1 is frozen at -20°C for 10 hours. The frozen product is then thawed at room temperature with ventilation, and after thawing, it is stirred and pulverized.
[0044] Step 3: Photoirradiation modification
[0045] The product from step 2 is subjected to multiple freeze-thaw cycles until its moisture content is below 30%. Then, it is spread out to a thickness of less than 5 cm and placed in the sun with a moisture content of 30-35% for more than 100 hours, turning it over every 10 hours. The average power density of the sunlight should be greater than 30 W / m2. Alternatively, ultraviolet laser irradiation for more than 50 hours can be used instead of sun exposure, turning it over every 5 hours. During laser irradiation, the laser power density should be greater than 50 W / m2 and the laser wavelength should be less than 300 nm. Water should be added to supplement the moisture content if it is insufficient during the modification process.
[0046] Step 4: Add the modified product from Step 3 to the thickener, flow modifier, pH adjuster, and water, and mix thoroughly to obtain the modified bentonite drilling fluid.
[0047] The photomodified powder is nano-ZnO or nano-TiO2 with a particle size of less than 200nm.
[0048] The freeze-thaw cycle must be performed at least 5 times. If the water content is below 30% during the freeze-thaw cycle, water must be added until the water content is 30%.
[0049] Example 2:
[0050] Combination Figure 3 The preparation method of the photomodified powder is as follows:
[0051] Step A: Mix industrial zinc oxide or titanium dioxide powder with 10 times its volume of water, wherein the purity of the zinc oxide and titanium dioxide raw materials is higher than 98%;
[0052] Step B: Place the product after mixing in step A in a stirrer and stir it at high speed. Then place it under an infrared pulsed laser for ablation preparation. The laser single pulse energy is required to be greater than 100 J / cm2, the laser repetition frequency is greater than 500 Hz, the ablation time is greater than 10 hours, and the particle size is processed until it is less than 200 nm.
[0053] Step C: Dry the product from step B.
[0054] Example 3:
[0055] Combination Figure 2 The preparation method of the photomodified powder is as follows:
[0056] Step A: Mix industrial zinc powder or titanium powder with 15 times its volume of water, wherein the purity of the zinc powder or titanium powder raw materials is higher than 95%;
[0057] Step B: Place the product from Step A into a stirrer and stir it at high speed. Then place it under an infrared pulsed laser for ablation. The laser single pulse energy should be greater than 100 J / cm2, the laser repetition frequency should be greater than 500 Hz, and the ablation time should be greater than 10 hours. Process until the particle size is less than 200 nm. Keep the water temperature below 30℃ during ablation.
[0058] Step C: Dry the product from step B.
[0059] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing modified bentonite drilling fluid for drilling, Bentonite drilling fluid comprises the following components: bentonite, viscosifier, filtration reducer, flow modifier, plugging agent, weighting agent, light modifier, pH adjuster, lubricant, and water. The photomodified powder is nano-ZnO or nano-TiO2 with a particle size of less than 200nm; The tackifier is one or more of xanthan gum, amine oxide, and polyvinylpyrrolidone; the filtration loss reducer is one or more of sulfomethylphenol resin and lignite resin; the flow pattern regulator is polyamide LH-OWA or polyamide LH-ORM; the weighting agent is barite; the photomodifying powder is nano-ZnO or nano-TiO2; the pH adjuster is a mixture of sulfuric acid, polyvinyl alcohol, sodium silicate, and sodium carbonate; and the lubricant is graphite powder or silica nanospheres. By weight, the ingredients are: 5-8 parts bentonite, 2-3 parts thickener, 2-3 parts filtration loss reducer, 3-5 parts flow modifier, 2-5 parts sealing agent, 40-50 parts weighting agent, 10-15 parts light-modifying powder, 5-8 parts pH adjuster, 1-2 parts lubricant, and 100 parts water. Its features The preparation method includes the following steps: Step 1: Mix and stir the raw materials First, mix bentonite, filtration loss reducer, sealing agent, lubricant, weighting agent and light-modifying powder. After mixing, use a high-speed mixer to stir and mix for more than 1 hour. Then add an equal weight of water and mix. Stir for more than 1 hour after mixing. Step 2, Freeze-forming The mixture obtained in step 1 is frozen at -20°C for 10 hours. The frozen product is then thawed at room temperature with ventilation, and after thawing, it is stirred and pulverized. Step 3: Photoirradiation modification The product from step 2 is subjected to 5 freeze-thaw cycles until its moisture content is below 30%. Then, it is spread out in a layer less than 5 cm thick and placed in sunlight with a moisture content of 30-35% for at least 100 hours, turning it over every 10 hours. The average solar power density must be greater than 30 W / m². 2 Alternatively, ultraviolet laser irradiation for more than 50 hours can be used instead of sun exposure, with the plant turned over every 5 hours; the laser power density during irradiation must be greater than 50W / m². 2 The laser wavelength is less than 300nm. Water should be added to replenish the moisture content if it is insufficient during the modification process. Step 4: Add the modified product from Step 3 to the thickener, flow modifier, pH adjuster, and water, and mix thoroughly to obtain the modified bentonite drilling fluid. The preparation method of photomodified powder is as follows: Step A: Mix industrial zinc oxide or titanium dioxide powder with 15 times its volume of water, wherein the purity of the zinc oxide and titanium dioxide raw materials is higher than 98%; Step B: Place the product from Step A in a stirrer and stir it at high speed. Then, place it under an infrared pulsed laser for ablation, requiring a single laser pulse energy greater than 100 J / cm². 2 The laser repetition frequency is greater than 500Hz, the ablation time is greater than 10 hours, and the processing is carried out until the particle size is less than 200nm. Step C: Dry the product from step B; The infrared laser is a carbon dioxide laser.
Citation Information
Patent Citations
Organobentonite production method
CN103482638A
Preparation method of organic bentonite
CN107777696A
Drilling fluid for inhibiting hydration of clay surface and preparation method of drilling fluid
CN108165244A